Multimodal Remote Sensing Applications in the Etruscan-Roman City of Vulci. (17th November 2022) - Forte, Maurizio; Trinks, Immo; Hinterleitner, Alois; Klein, Michael; LoPiano, Antonio; McCusker, Katherine; Schiel, Hannes; Schlögel, Ingrid; Trausmuth, Tanja; Vonkilch, Alexandra; Wallner, Mario; Neubauer, Wolfgang
ABSTRACT: Vulci (Viterbo Province, Italy) was one of the most important Etruscan city-states in the 1st millennium b.c . and became a Roman city in 280 b.c . The habitation site had over 1500 years of continuous life and a very large funerary area around the volcanic plateau. An international research cooperation investigated the site in 2014–2019 using remote sensing technologies and conducting archaeological excavations in the urban area. This paper presents the integrated application of remote sensing methods, which include multispectral unmanned aerial vehicles, aerial photography, and high-resolution georadar measurements. The multimodal application of active and passive sensors permitted a multilayered identification of archaeological features and led to substantial new interpretations of the rich archaeological landscape, which calls for a reconsideration of traditional scholarly narratives of Vulci's history.